2019
DOI: 10.1101/19008680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a differential diagnosis of cochlear synaptopathy and outer-hair-cell deficits in mixed sensorineural hearing loss pathologies

Abstract: Damage to the auditory periphery is more widespread than predicted by the gold-standard clinical audiogram. Noise exposure, ototoxicity and aging can destroy cochlear inner-hair-cell afferent synapses and result in a degraded subcortical representation of sound while leaving hearing thresh- olds unaffected. Damaged afferent synapses, i.e. cochlear synaptopathy, can be quantified using histology, but a differential diagnosis in living hu- mans is difficult: histology cannot be applied and existing auditory evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 89 publications
0
22
1
Order By: Relevance
“…This is important because a strong baseline EFR response will be more sensitive to changes induced by alterations in the ANF population. At the same time, we adopt an optimized analysis 140 method which extracts all the relevant envelope-following components from the raw EEG recordings (Vasilkov & Verhulst, 2019). Furthermore, we studied how OHC functionality affects the EFR generators to different stimulation paradigms to evaluate which EFR markers are differentially sensitive to synaptopathy, even when OHC damage is simultaneously present.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because a strong baseline EFR response will be more sensitive to changes induced by alterations in the ANF population. At the same time, we adopt an optimized analysis 140 method which extracts all the relevant envelope-following components from the raw EEG recordings (Vasilkov & Verhulst, 2019). Furthermore, we studied how OHC functionality affects the EFR generators to different stimulation paradigms to evaluate which EFR markers are differentially sensitive to synaptopathy, even when OHC damage is simultaneously present.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a dependency of the scalp-recorded AEP magnitude to head size, sex and age (Trune et al, 1988; Mitchell et al, 1989; Makary et al, 2011) and possible coexisting aspects of CS and OHC damage (Parthasarathy and Kujawa, 2018; Vasilkov and Verhulst, 2019). Hence, the spread of data-points within different recorded test-groups and spectral bandwidths could be explained by subject-specific factors unrelated to hearing or hearing-related factors associated with the main factors for grouping: (i) self-reported hearing difficulties in noisy environments in the first experiment, (ii) age and (iii) elevated hearing thresholds in the second experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Since OHC-damage and CS might both affect the EFR magnitude (Garrett and Verhulst, 2019; Vasilkov and Verhulst, 2019), we employed a computational model of the auditory periphery to simulate how different degrees of CS affected the EFR PtN magnitude, both in presence and absence of high-frequency sloping OHC-loss above 1 kHz (simulated high-frequency sloping audiograms in Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations